2006
DOI: 10.1001/archotol.132.6.579
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase and Lipoxygenase Enzymes in Nasal Polyps of Aspirin-Sensitive and Aspirin-Tolerant Patients

Abstract: Objective: To evaluate the expression of cyclooxygenase (COX) and lipoxygenase (LO) enzymes in nasal polyp specimens from aspirin-sensitive (AS) and aspirintolerant (AT) patients.Design: Immunohistochemical staining of archived tissue.Subjects: Specimens from 26 patients (11 AS and 15 AT) with nasal polyps were analyzed; specimens from 4 patients were used as controls.Interventions: Immunohistochemical techniques were used to evaluate the expression of the enzymes COX-1, COX-2, 5-LO, 12-LO, and 15-LO in nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
2
13
1
6
Order By: Relevance
“…Altered regulation of COX-2 and PGs has been suggested by a few recent reports to play an important role in the pathogenesis of CRS [1,21]. Our findings presented here further describe the expression and localization of COX-2 in CRS mucosa.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Altered regulation of COX-2 and PGs has been suggested by a few recent reports to play an important role in the pathogenesis of CRS [1,21]. Our findings presented here further describe the expression and localization of COX-2 in CRS mucosa.…”
Section: Discussionsupporting
confidence: 84%
“…Owens et al [21] found more COX-2 protein staining in CRS polyps of both aspirin-tolerant and -intolerant patients than normal mucosa by immunohistochemical assay. Consistent with these findings, we observed that increased expression of both COX-2 protein and mRNA in the nasal polyps in comparison to those of the controls.…”
Section: Discussionmentioning
confidence: 98%
“…Current data suggest that the decrement in response was blocked in these particular groups of patients. Recent studies showed a consistent decreased mRNA expression of COX‐2 enzyme on nasal polyp tissue of patients with AERD, which could explain the inhibited response to aspirin in terms of generation of 15‐epi‐LXA 4 [39–41]. Decreased NFκβ activity has been shown to be a reason for decreased expression of COX‐2 in this group of patients [42].…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have not found any differences in leukotriene C 4 (LTC 4 ) release from nasal polyp‐cultured cells (83) and the generation of COX and lipoxygenase (LO) products from whole blood cells between aspirin‐sensitive and ‐tolerant patients (93), while others have observed an increased generation of leukotriene‐producing enzymes (5‐LO and LTC 4 synthase), cysLTs in nasal polyp tissue in aspirin‐sensitive patients (80, 92, 94, 95). Moreover, increased expression of cysLT 1 receptors in the nasal mucosa from aspirin‐sensitive patients was found (96, 97).…”
Section: Eicosanoids and Aspirin‐exacerbated Respiratory Diseasementioning
confidence: 99%